Component Separation vs. Bridged Repair for Large Ventral Hernias: A Multi-Institutional Risk-Adjusted Comparison, Systematic Review, and Meta-Analysis - Holihan, Julie L. (Surg Infect (Larchmt), 2016)
Background: Repair of large ventral hernia defects is associated with high rates of surgical site occurrences (SSO), including surgical site infection (SSI), site dehiscence, seroma, hematoma, and site necrosis. Two common operative strategies exist: Component separation (CS) with primary fascial closure and mesh reinforcement (PFC-CS) and bridged repair (mesh spanning the hernia defect). We hypothesized that: (1) ventral hernia repair (VHR) of large defects with bridged repair is associated with more SSOs than is PFC, and (2) anterior CS is associated with more SSOs than is endoscopic, perforator-sparing, or posterior CS. Methods: Part I of this study was a review of a multi-center database of patients who underwent VHR of a defect ≥8 cm from 2010–2011 with at least one month of follow-up. The primary outcome was SSO. The secondary outcome was recurrence. Part II of this study was a systematic review and meta-analysis of studies comparing bridged repair with PFC and studies comparing different kinds of CS. Results: A total of 108 patients were followed for a median of 16 months (range 1–50 months), of whom 84 underwent PFC-CS and 24 had bridged repairs. Unadjusted results demonstrated no differences between the groups in SSO or recurrence; however, the study was underpowered for this purpose. On meta-analysis, PFC was associated with a lower risk of SSO (odds ratio [OR] = 0.569; 95% confidence interval [CI] = 0.34–0.94) and recurrence (OR = 0.138; 95% CI = 0.08–0.23) compared with bridged repair. On multiple-treatments meta-analysis, both endoscopic and perforator-sparing CS were most likely to be the treatments with the lowest risk of SSO and recurrence. Conclusions: Bridged repair was associated with more SSOs than was PFC, and PFC should be used whenever feasible. Endoscopic and perforator-sparing CS were associated with the fewest complications; however, these conclusions are limited by heterogeneity between studies and poor methodological quality. These results should be used to guide future trials, which should compare the risks and benefits of each CS method to determine in which setting each technique will give the best results.